Foresight methodologies useful to veterinary services - Grace, Delia (World Organisation for Animal Health, 2021)
The world is facing a broad range of challenges related to agriculture, and particularly the livestock sector, including threats to productivity, the natural environment and human health. While much research has been conducted into potential risks and their drivers, the 2020 COVID-19 pandemic demonstrated how governments can be affected by shocks that are to some extent predictable but for which they are often ill prepared. Policy seeks to anticipate and also influence the future and, as policy-makers, national Veterinary Services have an important role in both anticipating and influencing the future of their countries and the world. In the first part of this paper, the author summarises a wide range of Foresight methodologies and tools relevant to, or used by, Veterinary Services or veterinary researchers. This discussion is followed by an example of the adaptation and application of a Foresight framework tailored specifically to Veterinary Services. Finally, the author draws conclusions on Foresight methodologies useful to Veterinary Services.